Effective thermal-electric control system for hydrogen production based on renewable solar energy - (:unkn) unknown (Elsevier BV, 2024)
This paper focuses on the design and use of a control system for a renewable energy production plant based on hydrogen. The proposed control system aims at ensuring the stability and smooth functionality of the plant, which consists of a (i) photovoltaic...
Keywords: Hidrógeno; Energía solar